2001
DOI: 10.1302/0301-620x.83b4.11153
|View full text |Cite
|
Sign up to set email alerts
|

The cross-sectional area of supraspinatus as measured by diagnostic ultrasound

Abstract: We have established a reference standard for the cross-sectional area (CSA) of supraspinatus as measured by diagnostic ultrasound. The influence of hand dominance and of ageing on the CSA was also assessed. We examined 72 subjects aged from 20 to 79 years. Standard values of the CSA were determined with a high measure of interobserver reliability. Although the CSA on the dominant side was significantly larger (p < 0.001) by 0.16 cm2 (95% CI 0.072 to 0.249) than that on the non-dominant side, this difference ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Katayose and Magee 18 reported an influence of hand dominance on supraspinatus tendon thickness. Serafini et al 4 found no significant difference between right and left hands regarding FFT thick-ness.…”
mentioning
confidence: 99%
“…Katayose and Magee 18 reported an influence of hand dominance on supraspinatus tendon thickness. Serafini et al 4 found no significant difference between right and left hands regarding FFT thick-ness.…”
mentioning
confidence: 99%
“…They concluded that US is a valid and reliable method to assess the CSA of specific muscles in the hand and this correlates with strength measurements. Katoyose and Magee [21] reported measurement reference standards of CSA of supraspinatus by diagnostic ultrasound in 72 volunteers. They also found that the CSA of the dominant side was significantly larger than the non-dominant side with a high measure of inter-observer reliability.…”
Section: Discussionmentioning
confidence: 99%
“…To date, in vivo US studies investigating supraspinatus (SP) have focused on gross morphological features such as cross-sectional area and MT (Juul-Kristensen et al, 2000;Dupont et al, 2001;Katayose and Magee, 2001). However, these features were investigated only in the relaxed state with the shoulder positioned in neutral rotation and 08 abduction.…”
Section: Introductionmentioning
confidence: 99%